Constellation of Liberty - Christy Davis (Symphony in the Flint Hills, 2019)
Introduction: Ad Astra Per Aspera. By the time John J. Ingalls first inscribed these words on the Kansas Seal in 1861, the new state had endured seven years of territorial hell.